Integrating Generative AI (e.g., ChatGPT) as a Collaborative Writing Partner in an Academic English Course: A Pedagogical Study - Iin Almeina; Ava Lee; Marcus Tan; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
Background. Traditional writing instruction often struggles to provide continuous feedback, individualized support, and opportunities for iterative revision, leading to gaps in students’ development of critical thinking and academic discourse skills. Generative Purpose. This study investigates the pedagogical impact of integrating ChatGPT as a collaborative writing partner in an Academic English course. Method. Employing a mixed-methods design, the study involved 36 university students who participated in a six-week intervention consisting of guided writing tasks, AI-supported drafting sessions, and reflective activities. Results. The findings indicate noticeable improvements in coherence, lexical precision, and argumentative structure, accompanied by increased student confidence and metacognitive engagement. Participants viewed ChatGPT as a supportive partner that enhanced idea generation and revision processes, although concerns regarding overreliance and critical evaluation emerged. Conclusion. The study concludes that generative AI can serve as an effective pedagogical tool when integrated with explicit instruction and human guidance.